Blended problem-based learning: Designing collaboration opportunities for unguided group research through the use of Web 2.0 tools - Walker, Richard (Proceedings of the International Conference on Networked Learning, 2012)
This paper reports on the evaluation findings for a postgraduate Law programme following a problem-based learning (PBL) curriculum, which introduced group wiki and blogging tools for students to use in support of a series of unguided group research activities. Following a face-to-face PBL session where students were presented with a new problem and brainstormed learning outcomes and tasks as a framework to solve it, the virtual tools were then employed to support discussion and sharing of research outside the classroom, leading to the production of a collaborative solution by the group. The problem-based exercises targeted higher order thinking, with students encouraged to demonstrate skills in articulating and explaining the solutions they had reached in relation to the case problem, as well as negotiating and interpreting issues. This paper considers the online stage of the PBL process, looking at the reception of the study methods for the research activity and the effectiveness of the web tools in supporting the unguided group research tasks. Evaluation focused on levels of student engagement during the performance of the research tasks and the nature of the online learning exchanges to see whether they reflected the higher-order thinking which had been targeted by the course instructor in the PBL exercises. Findings are drawn from a mixed-mode evaluation of the first delivery of this course in 2009, carried out through activity logs, content analysis of blog posts and focus group interviews. The results reveal a positive reception for the learning methods and tools with evidence of higher order thinking and reflective skills in the logged exchanges as students became accustomed to the new learning methods. The pattern of contributions gradually evolved from 'one-shot' postings of solutions to critiques of peer contributions and revision of original posts, demonstrating collaborative working between group members towards an agreed solution. However, this study highlights the challenges for instructional support in the management of the learning process for these tasks - specifically in addressing students' anxiety over their performance in the online tasks and a perceived need for individual and collective feedback in support of the unguided research task. Getting the balance right in providing facilitation rather than direction in the conduct of the unguided research tasks, whilst providing adequate feedback on student performance, remains a challenge for PBL tutors and a theme for further research.